Contrastive Analysis of Noun Phrase between English and Bugis Language - Malabar, Fahria; Wardatulljannah, Besse; Bay, Indri Wirahmi (Universitas Negeri Gorontalo, 2023)
This study aims to explore the similarities and differences in noun phrase structures between the English and Bugis languages. Using a documentation technique, the research selectively extracts data from the literature, specifically books and articles that focus on noun phrases. The researchers systematically collect and examine the data using the contrastive analysis technique. The findings reveal both similarities and differences in the form, structure and function of noun phrases between English and Bugis. Common features in both languages include numerals, demonstratives and quantifiers as modifiers preceding the noun (head), while prepositional phrases are positioned after the noun (head). Conversely, in English, articles, adjectives, possessives and ordinals precede the noun (head), whereas in Bugis they follow the noun (head). Relative clauses in English and Bugis have different structures and functions. Therefore, a contrastive analysis of noun phrases between English and Bugis proves to be very beneficial for learners, as it increases their awareness of the unique characteristics of both languages, especially in terms of their structural and functional aspects.